Implementasi Model Pembelajaran Tipe STAD (Student Team Achievement Division) Terhadap Kemampuan Menulis Paragraf Kelas IV SDN 8 Kota Sorong - Nurhikmah Nurhikmah; Untari Untari; Tusana Nurul Safaah; Reni Permata; Siti Nurjannah; Jenro P Sijabat; Hafsah Safitri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study was to find out how the STAD learning model influences the ability to write readings in 20 grade IV students at SDN 13 Betung, Banyuasin Regency. Through extensive data collection, this qualitative research strategy aims to provide a comprehensive explanation of a phenomenon. The significance of phenomena and the importance of observing them is the main focus of qualitative research methods. In this paragraph, the students' goals for improving their learning of Indonesian are: 1) students can express considerations, presumptions, conjectures, and feelings stored in printed copies in a straightforward manner;(2) Students are able to write about the situation and context in their writing; 3) Students like to write; 4) Students can use linguistic elements in writing literary works. Writing can also be understood as expressing one's feelings, thoughts and intentions to others. Writing is a way to generate ideas and emotions through writing.